FACTORS AFFECTING THE OUTCOMES OF DIRECT PULP CAPPING WITH MINERAL TRIOXIDE AGGREGATE IN PERMANENT TEETH (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors influencing the outcomes of direct pulp capping using Mineral Trioxide Aggregate (MTA) in permanent teeth.Materials and Methods: A prospective cohort study was conducted on 100 vital permanent teeth treated with direct pulp capping using MTA at 108 Military Central Hospital from January 2023 to September 2024. The investigated variables included age, sex, tooth type, dental arch location, cause and size of pulp exposure, time from exposure to treatment, and isolation method. Clinical and radiographic outcomes were evaluated at 6 and 12 months. At the 6-month follow-up, 95 teeth were re-examined, and 90 teeth completed the 12-month follow-up. Data were analyzed using the Chi-square test or Fisher’s exact test and logistic regression analysis (p < 0.05).Results: The overall success rate was 91% (91/100). Significant factors associated with treatment outcomes included the cause of pulp exposure (p = 0.03), size of pulp exposure (p = 0.02), and isolation method (p = 0.001).Conclusion: Direct pulp capping with MTA showed a high success rate when appropriate case selection was applied, particularly in cases with small pulp exposure and adequate infection control using rubber dam isolation.
Keywords: direct pulp capping, MTA, influencing factors, permanent teeth, vital pulp therapy.